Contribuciones a la flora vascular de la provincia de Málaga (Andalucía, España) - Casimiro-Soriguer Solanas, Federico; Cabezudo Artero, Baltasar (Acta Botanica Malacitana, 2018)
Contribuciones a la flora vascular de la provincia de Málaga (Andalucía, España)